Diversifikasi Produk Dan Strategi Digital Marketing Bagi UMKM Oemah Singkong Untuk Daya Saing Berkelanjutan - Ade Rizki Rinaldi; Sandy Eka Permana; Ahmad Najib Yahya; Luthfi Adianto (CV. Multi Kreasi Media, 2024)
This community service program aims to enhance the competencies of vocational high school (SMK) students in web development through Junior Web Developer training. The activities were carried out at several SMKs in Cirebon Regency and Cirebon City as an effort to bridge the gap between school curricula and industry needs. The implementation methods included preparation and planning, training execution, monitoring and evaluation, as well as dissemination of results. The outcomes of this program showed a significant improvement in students’ understanding and skills in web development technologies, particularly in the use of HTML, CSS, JavaScript, and modern frameworks. In addition, the participating teachers also benefited from workshops designed to enhance their ability to teach industry-based materials. This program successfully produced several outputs such as learning modules, student web projects, and collaborations with industry partners to open job opportunities for graduates. Through this program, it is expected that vocational students will be better prepared to face the workforce and the digital industry. The sustainability of this program can be expanded by increasing the number of industry partners and broadening the scope of training participants.